Proposals for Legislative Solutions to the Problems of Bird Deaths on Overhead Power Lines in Kazakhstan - Nurlan Kh. Ongarbayev (Пернатые хищники и их охрана, 2023)
The problems of bird deaths on overhead power lines (PLs) have been studied by experts for many years and have now been examined enough to make basic conclusions about the causes of their deaths and possible ways of solving this problem. It is no secret that PLs that are dangerous to birds cause the greatest damage to migrating and/or nomadic birds. Thus, the states that have not solved the issues of mass deaths of birds on OPLs in their countries, in fact, violate the provisions of the international convention on the conservation of migratory species of wild animals (Bonn Convention or CMS), if they have acceded to this convention.